New-onset type 1 diabetes mellitus in the Paediatric Emergency Department: impact of the COVID-19 pandemic - Raquel García Romero; Laia Baleta Riera; Nuria Sanz Marcos; Vanessa Arias Constanti; Victoria Trenchs Sainz de la Maza; Carles Luaces (Korean Society of Pediatric Endocrinology, 2023)
Purpose On the 14th of March 2020, the Spanish government decreed a state of alarm due to the coronavirus disease 2019 (COVID-19) pandemic, directly affecting healthcare. This situation led to delayed diagnosis of several serious diseases, and its impact on many diseases such as the onset of type 1 diabetes mellitus (T1DM) remains unknown. The aim of this study is to determine the impact of the COVID-19 pandemic on the onset of T1DM in children. Methods A descriptive-observational study was performed using data from children younger than 18 years (n=115) admitted with diagnosis of T1DM. We compared the 8 months from May-December 2020 to the same timeframe in 2019. Results Our data show an increase of newly attended cases of T1DM in 2020, due to referral of Catalan children with onset of diabetes to our centre. Moreover, fewer patients presented with simple hyperglycaemia at the onset of the COVID-19 period. Delay in consulting the hospital, decreased access to the healthcare system, and avoidance of hospitals to minimize exposure to COVID-19 could have contributed to this finding. There were no differences in the number of days of hospitalization (including days in the paediatric intensive care uniy) between the years. Conclusions The effects of the lockdown during the COVID-19 pandemic not only delayed the diagnosis of diabetes, but also its allowed time for its severity to increase. Future studies should focus on the influence of new variants of COVID-19 on the onset of T1DM during the postvaccination period.